Leeuwenhoekiella aestuarii sp. nov., isolated from salt-water sediment and first insights in the genomes of Leeuwenhoekiella species. Issue 3 (10th January 2020) - Tahon, Guillaume; Lebbe, Liesbeth; De Troch, Marleen; Sabbe, Koen; Willems, Anne
Abstract : Four Gram-negative, aerobic, rod-shaped and yellow-orange pigmented bacteria (R-46770, R-48165 T, R-50232 and R-50233) were isolated from intertidal sediment and water of the Westerschelde estuary between 2006 and 2012. Analysis of their 16S rRNA gene sequences revealed that the four strains form a separate cluster between validly described type strains of the genus Leeuwenhoekiella . DNA–DNA reassociation values of two representative strains (i.e. R-48165 T and R-50232) of the new group with type strains of Leeuwenhoekiella species ranged from 18.7 to 56.6 %. A comparative genome analysis of the two strains and the type strains confirmed average nucleotide identity values from 75.6 to 94.4 %. The G+C contents of the genomic DNA of strains R-48165 T and R-50232 were 37.80 and 37.83 mol%, respectively. The predominant cellular fatty acids of the four novel strains were summed feature 3 (i.e. C16 : 1 ω7 c and/or iso-C15 : 0 2-OH), iso-C15 : 0, iso-C15 : 1 G and iso-C17 : 0 3-OH. The four new Leeuwenhoekiella -like strains grew with 0.5–12 % (w/v) NaCl, at pH 5.5–9.0 and displayed optimum growth between 20 and 30 °C. Based on the results of phenotypic, genomic, phylogenetic and chemotaxonomic analyses, the four new strains represent a novel species of the genus Leeuwenhoekiella for which the name Leeuwenhoekiella aestuarii sp. nov. is proposed. The type strain is LMG 30908 T (=R-48165 T =CECT 9775 T =DSM 107866 T ). Genome analysis of type strains of the genus Leeuwenhoekiella revealed a large number of glycosyl hydrolases, peptidases and carboxyl esterases per Mb, whereas the number of transporters per Mb was low compared to other bacteria. This confirmed the environmental role of Leeuwenhoekiella species as (bio)polymer degraders, with a specialization on degrading proteins and high molecular weight compounds. Additionally, the presence of a large number of genes involved in gliding motility and surface adhesion, and large numbers of glycosyl transferases per Mb confirmed the importance of these features for Leeuwenhoekiella species.